Enhancing adoptive cancer immunotherapy with Vγ2Vδ2 T cells through pulse zoledronate stimulation. Issue 1 (21st February 2017) - Nada, Mohanad H.; Wang, Hong; Workalemahu, Grefachew; Tanaka, Yoshimasa; Morita, Craig T.
Abstract : Background: Human γδ T cells expressing Vγ2Vδ2 T cell receptors monitor foreign- and self-prenyl pyrophosphate metabolites in isoprenoid biosynthesis to mediate immunity to microbes and tumors. Adoptive immunotherapy with Vγ2Vδ2 T cells has been used to treat cancer patients with partial and complete remissions. Most clinical trials and preclinical studies have used continuous zoledronate exposure to expand Vγ2Vδ2 cells where zoledronate is slowly diluted over the course of the culture. Zoledronate inhibits farnesyl diphosphate synthase (FDPS) in monocytes causing isopentenyl pyrophosphate to accumulate that then stimulates Vγ2Vδ2 cells. Because zoledronate inhibition of FDPS is also toxic for T cells, we hypothesized that a short period of exposure would reduce T cell toxicity but still be sufficient for monocytes uptake. Additionally, IL-15 increases the anti-tumor activity of murine αβ T cells in mice but its effect on the in vivo anti-tumor activity of human Vγ2Vδ2 cells has not been assessed. Methods: Human Vγ2Vδ2 T cells were expanded by pulse or continuous zoledronate stimulation with IL-2 or IL-15. Expanded Vγ2Vδ2 cells were tested for their expression of effector molecules and killing of tumor cells as well as their in vivo control of human prostate cancer tumors in immunodeficient NSG mice. Results: Pulse zoledronate stimulation with either IL-2 or IL-15 resulted in more uniform expansion of Vγ2Vδ2 cells with higher purity and cell numbers as compared with continuous exposure. The Vγ2Vδ2 cells had higher levels of CD107a and perforin and increased tumor cytotoxicity. Adoptive immunotherapy with Vγ2Vδ2 cells derived by pulse stimulation controlled human PC-3 prostate cancer tumors in NSG mice significantly better than those derived by continuous stimulation, halting tumor growth. Although pulse zoledronate stimulation with IL-15 preserved early memory subsets, adoptive immunotherapy with IL-15-derived Vγ2Vδ2 cells equally inhibited PC-3 tumor growth as those derived with IL-2. Conclusions: Pulse zoledronate stimulation maximizes the purity, quantity, and quality of expanded Vγ2Vδ2 cells for adoptive immunotherapy but there is no advantage to using IL-15 over IL-2 in our humanized mouse model. Pulse zoledronate stimulation is a simple modification to existing protocols that will enhance the effectiveness of adoptively transferred Vγ2Vδ2 cells by increasing their numbers and anti-tumor activity.